2021
DOI: 10.1177/07435584211034874
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Premature Closure of a Mentoring Relationship: A Qualitative Study of Mentoring Youth With a Visual Impairment

Abstract: Preventing mentor-mentee relationships from ending prematurely is important because an early or unanticipated closure could lead to negative youth outcomes. In this study, the reasons for premature closure of a community-based mentoring program for youth with a visual impairment (VI) are studied. Data from 44 prematurely ended mentor-mentee pairs were analyzed; all mentees (mean age = 18.5, SD = 1.92) and 23 of the mentors had VI. Logbook data with two types of transcribed semi-structured interviews were thema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Regarding mentee−mentor matching, dyads with shared racial identity show a reduced risk for premature match closure . In contrast, research found an increased rate of premature match closure for dyads with a similar disability (i.e., visual impairment) (Heppe et al, 2019(Heppe et al, , 2021. Two studies (Kupersmidt et al, 2017a;Stelter et al, 2018) (DeWit et al, 2016).…”
Section: Previous Research On Reasons For Premature Match Closurementioning
confidence: 96%
See 4 more Smart Citations
“…Regarding mentee−mentor matching, dyads with shared racial identity show a reduced risk for premature match closure . In contrast, research found an increased rate of premature match closure for dyads with a similar disability (i.e., visual impairment) (Heppe et al, 2019(Heppe et al, , 2021. Two studies (Kupersmidt et al, 2017a;Stelter et al, 2018) (DeWit et al, 2016).…”
Section: Previous Research On Reasons For Premature Match Closurementioning
confidence: 96%
“…However, preventing premature match closure requires a comprehensive understanding of the reasons and underlying mechanisms leading to this phenomenon. | 3123 Heppe et al, 2019Heppe et al, , 2021Herrera et al, 2013;Kupersmidt et al, 2017aKupersmidt et al, ,2017bRaposa et al, 2016;Schwartz et al, 2011;Shlafer et al, 2009;Spencer et al, 2017Spencer et al, , 2018Spencer et al, , 2020Stelter et al, 2018). In these studies, either participants were surveyed or interviewed after or at the time of premature match closure about their experiences and their understanding of the reasons for mentoring termination, or mentoring programs were compared on various program characteristics to identify risk factors for premature match closure.…”
Section: Premature Match Closurementioning
confidence: 99%
See 3 more Smart Citations